Deceiving SARS-CoV-2 molecular-tropism clues – A combinational contemporary strategy. (November 2020) - Balaji, APB; Bhuvaneswari, Srinivasan; Kumar, D Nanda
Abstract: Several attempts to control the dreadfulness of SARS-CoV-2 are still underway. Based on the literature evidences we have speculated a prospective contemporary remedy, which was categorized into Specificity, Remedy, and a Conveyor. In which, pros and cons were discussed and inferred the possible alternatives. (a) Specificity: Implicit to express the ACE2 receptors in conveyor cells to deceive SARS-CoV-2 from prepone targets. (b) Remedy: As depletion of pulmonary surfactants causes strong acute respiratory distress syndrome, we propose an entity of a cost-effective artificial surfactant system as a remedy to pulmonary complications. (c) Conveyor: We propose red blood cells (RBCs) as a conveyor with embedded artificial surfactant and protruding ACE2 receptors for the target-specific delivery. Overall we postulate focused insights by employing a combinational contemporary strategy to steer towards a prospective direction on combating SARS-CoV-2.